공동주택의 화재조사 - 현장조사 및 연소실험에 의한 초기 화재확대과정 추정 - 남동군(Nam, Dong-Gun); 하세미유지(Hasemi, Yuji) (한국화재소방학회 논문지, 2009)
Identification of the exact cause of a building fire is generally difficult, because the source and initially ignited objects are often severely damaged or even lost during the early stages of the fire. We made an experimental attempt to reasonably estimate the burning during the very early stages of a fire, and identify its source and causes. The case we studied was an apartment fire, which occurred in Tokyo, in July 2002. The fire was extinguished just after flashover, and the on-site investigations suggested the fire started from the TV and TV stand, which had been damaged so severely that it was difficult to conclude that the TV was the ultimate cause of the fire, simply from the on-site investigation. We conducted a series of burn tests using a TV and other products identical to those actually used in the apartment. Tests were set-up and procedures were carefully studied to recreate the conditions of the articles that remained, and of the room itself. The tests demonstrated that the conditions in the apartment could be recreated only when the fire started inside the TV and came into close contact with dresser. 건축물 화재에서는 발화물과 주변 가연물이 소실하기 때문에 화재현장 조사만으로 출화원인을 규명하기 어렵다. 따라서 본 연구는 현장조사와 화재실험을 통해 화재의 원인과 확대과정을 추정하는 방법에 관하여 고찰하였다. 본 연구에서는 화재원인 불명으로 판단된 공동주택의 화재사례를 대상으로 현장의 잔존물에서 출화장소와 초기연소물을 추정하고, 출화물로 추정된 가연물을 대상으로 연소실험을 실행하여 출화원인 등을 추정하였다. 화재실험에서는 가연물의 종류 및 배치 등을 출화이전의 상태로 재현하고 출화조건을 가정하여 반복적으로 실행하여 연소 후의 상황과 화재현장의 잔존물을 비교함으로써 출화원인 및 초기 화재확대과정을 규명하였다.